Distribute to eliminate the parenthesis
x^2 + 2x + 6x + 12 = 60
Combine like terms
x^2 + 8x + 12 = 60
Subtract 60 from both sides
x^2 + 8x - 48 = 0
Factor the equation
(x+12)(x-4)=0
x+12=0
x+4=0
x= -12 and -4
Answer:70
Step-by-step explanation:
You do the inverse operation which would be subtraction and multiplication. You add the 6 to the 8 and you get 14. Then you would multiply 14 by 5 to get 70. Hope this helps :D
I think that the baby would weight 18 pounds if her weight doubles in six months
Answer:156
Step-by-step explanation:
Answer:
I believe the answer is - they are the same shape but different sizes